Spray drying encapsulation of red wine : stability of total monomeric anthocyanins and structural alterations upon storage - Álvarez Gaona, Izmari Jasel (2018)
Fil: Álvarez Gaona, Izmari J. Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina